Islamist Ideology and Its Effect on the Global Conflict: Comparative Study between Hamas and ISIS - Mulawarman Hannase (UIN Sunan Kalijaga Yogyakarta, 2019)
This paper aims to explain that the spread of the ideology of Islamism in the Middle East in recent decades has led to conflict, both intra and inter-religion that continues until today. From these Islamist groups, Hamas Movement and ISIS provided significant effects of the conflict are. This study is qualitative research. Conflict Theory of John Spanier (higt-politic conflict) used to analyze how the two groups model of ideological construction influenced the political and economic stability as well as conflict in the Middle East and the Islamic world. Based on the observations of these two groups, it can be found that theologically, Hamas adheres to religious doctrines which prompted him to undertake armed resistance against Israel. At the same time, ISIS is a militant group that is strongly influenced by religious doctrine. However, from the aspect of rigidity doctrine and strategy of the movement, both groups are much different. ISIS is an ultra-radical group hostile to all other communities and brutally attacked the community of which he considered infidels. While Hamas has a more soft ideology and commit acts of violence in the context of resistance against Israeli colonialism.[Makalah ini bertujuan untuk menjelaskan bahwa penyebaran ideologi Islamisme di Timur Tengah dalam beberapa dekade terakhir telah menyebabkan konflik, baik intra maupun antar-agama yang berlanjut hingga saat ini. Dari kelompok-kelompok Islam ini, Gerakan Hamas dan ISIS memberikan efek signifikan dari konflik tersebut. Penelitian ini adalah penelitian kualitatif. Teori Konflik John Spanier (konflik politik berskala tinggi) digunakan untuk menganalisis bagaimana model konstruksi ideologis kedua kelompok mempengaruhi stabilitas politik dan ekonomi serta konflik di Timur Tengah dan dunia Islam. Berdasarkan pengamatan kedua kelompok ini, dapat ditemukan bahwa secara teologis, Hamas menganut doktrin agama yang mendorong mereka untuk melakukan perlawanan bersenjata terhadap Israel. Pada saat yang sama, ISIS adalah kelompok militan yang sangat dipengaruhi oleh doktrin agama. Namun, dari aspek kekakuan doktrin dan strategi pergerakan, kedua kelompok jauh berbeda. ISIS adalah kelompok ultra-radikal yang memusuhi semua komunitas lain dan secara brutal menyerang komunitas yang dianggapnya sebagai orang kafir. Sementara Hamas memiliki ideologi yang lebih lunak dan melakukan tindakan kekerasan dalam konteks perlawanan terhadap kolonialisme Israel.]